(untitled) (Bangladesh Journal of Neuroscience, 2016)
Background: Carpal tunnel syndrome (CTS) is the most frequent compressive focal mononeuropathy found in clinical practice. Patients mostly experience pain, paresthesia, and less commonly, weakness in the median nerve distribution which badly affects dexterity and grip. Common risk factors include repetitive wrist movements, metabolic and degenerative diseases, connective tissue disease and pregnancy. Nerve conduction study is one of the most sensitive and specific tools to diagnose CTS. This study was aimed to grade the CTS cases according to the severity based on electrophysiological findings and explore its association with clinical presentation of diabetic patients had nerve conduction study at BIRDEM General Hospital. Materials and Methods: This observational study was done in the electro diagnostic clinic of Neurology department, BIRDEM during the period Sept 2015 to Feb 2016. The study included 100 hands of 84 patients suffering from CTS consecutively attending the clinic. All the patients were interviewed and clinically examined. Demographic data including age, gender, occupation, affected hand and hand dominance along with duration of disease were recorded. Patients were graded according to clinical history and objective findings and again based on the Canterbury NCS Severity Scale. Results: Of these 84 diabetic patients presenting with impression of CTS 96% were females. Mean age of the study subjects was 49.6±10.1 (28-85). Most of the female patients were housewives. Clinical grading of CTS was as follows: mild symptoms in 54.76%, moderate symptoms in 23.8% and severe symptoms in 28.58% patients. According to The Canterbury NCS Severity Scale out of total 100 hands,3.5% had Grade 2 (Mild ) 30.5%had Grade 3 (Moderate) ,29.4 % had Grade 4 (Severe), 34.1% had Grade 5 (Very severe) disease. Only 2 patients had Grade 6 (extremely severe) lesion. Of the study subjects 22 (26.19%) had bilateral and rest (73.81%) had unilateral disease. Conclusion: Data demonstrated female preponderance of the diabetic CTS cases of middle age. Proportional graded deterioration of electrophysiological parameters along with the clinical severity grades highlights the fact that NCS provide additional and independent objective evidence in the diagnosis and severity assessment of CTS and plausibly has important role in prioritizing treatment plan. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 98-105